New Zealand's Accident Compensation Scheme and Chronic Pain Syndrome - Bull, Juliet (Victoria University of Wellington Law Review, 2014)
Chronic pain syndrome does not currently constitute a physical injury under New Zealand's Accident Compensation scheme. This article considers the correctness of this exclusion given the Supreme Court's adoption in Allenby v H of an expanded interpretation of the term "physical injury", in deeming pregnancy to be an injury. It concludes that policy factors, particularly the need to uphold the integrity of the legislation enacted by Parliament, demand that the exclusion of chronic pain syndrome is maintained.